Field Measurements Of Overburden And Chain Pillar Response To Longwall Mining (22054dce-c5fa-459f-94f1-b6ef58bd87bf) - Daniel W. H. Su (International Conference on Ground Control in Mining, 1987)
This paper presents the results of an extensive geomechanical testing and monitoring program conducted at a longwall panel. The field program included the monitoring of roof caving sequence and mechanism, surface subsidence, change of pillar stress, roof displacement and entry convergence, and strength characterization of the overburden rocks. The response of eight headgate pillars and the adjacent entries was monitored as the longwall face approached and passed the instrumented locations. Overburden response to longwall mining was monitored using time domain reflectometry (TDR) technology; and, the height of the highly fractured zone above the gob was determined by postmining drilling. Good correlation was found between the height of the highly-fractured zone and the TDR, subsidence, and pillar stress data. The results provide a detailed picture of the response of overburden strata and chain pillars to longwall mining. A preliminary model representing the overburden strata behavior at the test site in response to the longwall mining is proposed.